Walnut shell based adsorbents: A review study on preparation, mechanism, and application - Hania Albatrni (17092945) (2022)
Agricultural-based adsorbents have received an upsurge of interest in the water treatment industry especially in the area of adsorption. They have been widely investigated as the next generation adsorbents due to their unique physio-chemical properties and high affinity towards a wide variety of constituents ranging from organic compounds to heavy metal ions. In addition, agricultural-based adsorbents are now a cheaper and sustainable option as opposed to non-renewable and expensive adsorbents originating from coal, polymers, and petroleum residues. Among different agriculture wastes available, walnut shells exhibit great potential as activated carbon precursor. They have outstanding chemical stability, high surface area and low ash content. In this review, walnut shell-based adsorbents have been assessed in terms of their activation methods and preparation. Furthermore, adsorbents' resulting characteristics and factors influencing the adsorption capacity have been summarized and thoroughly analyzed. It has been determined that the adsorption efficiency is heavily associated with the characteristics of the adsorbent including pore diameter, surface area, surface functional groups and the nature of the background solution including pH, temperature and ionic strength. This review identifies different activation methods reported in the literature including chemical and physical activation and chemical impregnation and functionalization. The literature survey also entails a comprehensive discussion involving types of mechanisms and factors controlling adsorption behaviors towards targeted contaminants. Moreover, a detailed analysis of adsorption isotherms and kinetics involved in the adsorption process is also included. Finally, this review mentions future research needs and challenges of adsorption by walnut shell-based adsorbents. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2021.102527